Penggunaan Aplikasi E-Office dalam Pengelolaan Arsip Elektronik di Kantor Wilayah Direktorat Jendral Perbendaharaan Sumatera Barat - Tuzzahra, Raudya; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2020)
AbstractThe purpose of this paper is to describe the process of creating a cultural literacy package in Kampung Batu Fishermen Village, Batang Arau, Padang Selatan, Padang City. This research uses a descriptive method. Data was collected through a literature review as well as direct observation and interviews with the Chairman of the RW, fishermen, and community leaders in Kampung Batu Fishermen Village located in RW II, Batang Arau Sub-District, Padang Selatan District, Padang City. Based on research that has been done can be concluded as follows. Making this information package is done through five stages. First, the culture of fishing communities in Kampung Batu Fishermen Village, Batang Arau, Padang Selatan, Padang City, among others: (1) Gender system; (2) Labor Agent-Fisherman Relations; (3) patterns of resource exploitation; (4) Social leadership. Secondly, the creation of a Culture literacy information package in Kampung Batu Fishermen Village, Batang Arau, South Padang, Padang City is carried out through five stages, namely: (1) Establishing the topic and type of information package packaging; (2) information gathering; (3) Analysis of the results of information gathering; (4) packaging information; (5) Evaluation of information packages. The explanation of the results of the manufacturing process is as follows: Determine the topic and type of information package packaging, the topic raised is Cultural Literacy in the Kampung Batu Fishermen Village, Batang Arau, South Padang, Padang City which is packaged in a printed information package; Information gathering is done by interview and direct observation to the Kampung Batu Fisherman Village. In addition, it is necessary to search the literature so that the data obtained for an information package becomes a product that presents true and relevant information; Analysis of the results of information gathering. From the information gathering, it is known that what is considered important as a cultural identity builder of fishing communities such as gender systems, patron-client relations, patterns of resource exploitation, and social leadership; Packaging information, done by presenting information that has been obtained from gathering information in the form of an information package; Evaluation of the information package is done by submitting a questionnaire to 10 respondents and it is known that 92.4% of respondents strongly agree that the cultural literacy information package is interesting, informative and has benefits for its users.Keywords: e-office, electronic archive.